Architecture and cityscapes tips and techniques for drawing on location - Campanario, Gabriel (The urban sketching handbook, 2014)
"Award-winning illustrator Gabriel Campanario first introduced his approach to drawing in The Art of Urban Sketching, a showcase of more than 500 sketches and drawing tips shared by more than 100 urban sketchers around the world. Now, he drills down into specific challenges of making sketches on location, rain or shine, quickly or slowly, and the most suitable techniques for every situation, in The Urban Sketching Handbook series. It's easy to overlook that ample variety of buildings and spaces and the differences from city to city, country to country. From houses, apartments and shopping malls to public buildings and places of worship, the structures humans have created over the centuries, for shelter, commerce, industry, transportation or recreation, are fascinating subjects to study and sketch.In The Urban Sketching Handbook: Architecture and Cityscapes, Gabriel lays out keys to help make the experience of drawing architecture and cityscapes fun and rewarding. Using composition, depth, scale, contrast, line and creativity, sketching out buildings and structure has never been more inspirational. This guide will help you to develop your own creative approach, no matter what your skill level may be today. As much as The Urban Sketching Handbook: Architecture and Cityscapes may inspire you to draw more urban spaces, it can also help to increase your appreciation of the built environment. Drawing the places where we live, work and play, is a great way to show appreciation and creativity"--